Technical report: solving the SIRC model of the Influenza A by using Forth Order Runge Kutta method / Azida Shaharuddin, Nurul Aisyah Haja Muhaiadin and Suhaifaniza Fasya Saiful Anuar - Shaharuddin, Azida; Haja Muhaiadin, Nurul Aisyah; Saiful Anuar, Suhaifaniza Fasya (2016)
The best mathematical model to explain H1N1 disease is SIRC model which is in the form of system of Ordinary Differential Equation (ODE). Parameters used in the ordinary differential equation (ODE) are different as the surrounding of H1N1 are different. Hence, the accuracy of SIRC model depends on parameters. The main objective of this project is to solve the mathematical model for H1N1 in order to calculate population and to observe the trend of solutions if different parameters are used. Rungge-Kutta method is applied in solving the system of ordinary differential equations SIRC model since previous studies proved that there is no analytical solution for the SIRC model. For the conclusion of this project, the best SIRC model with the most appropriate parameters is identified.